Modeling Pepper Drying by Jet Spouted Bed Technique Using ANFIS System - สถาพรประสาธน์ กิตติ (Srinakharinwirot University Engineering Journal, 2018)
This research aimed to determine the drying model of pepper undergoing a jet spouted bed drying process. A comparative study was executed among experimental results and empirical models and adaptive-network-based fuzzy inference system (ANFIS). Pepper was dried under drying temperatures of 70, 80 and 90 °C, hot air velocity 20 m/s, bed height 250 mm. ANFIS input were air drying temperature and drying time and output was moisture ratio. The results showed that, the ANFIS had better capability than the empirical models. The best ANFIS model was model no.8 withthe coefficient of determination (R2) and root-mean-square error (RMSE) are 0.9991 and 0.0032 respectively. Among empirical drying models considered, the page model, was found to best describe the drying behavior of pepper, the coefficient of determination (R2) and root-mean-square error (RMSE) are 0.9983 and 0.0067 respectively.